Décaler les approches de la durabilité et des territoires : regards croisés sur les 20 ans de la rubrique « Points de vue » - Rhoda Fofack-Garcia; Rémy Petitimbert; Leslie Carnoye; Thibault Boughedada; Anne-Ryslène Zaoual (Développement Durable et Territoires)
The 20th anniversary issue of Développement Durable & Territoires (Sustainability & territories) provides an opportunity to highlight the ambitions of the « Point de vue » (Viewpoints) section and to review its history. The section was conceived as an original one, aiming to allow the expression of « points de vue » on subjects or objects related to the editorial line of DD&T, in a freer format than that of standard scientific articles and/or from non-academic actors. This introduction looks back at the highlights of the section and sheds light on the type of publication it contains. The contributions of the section are highlighted, but also the difficulty inherent in the objective : in the end, few publications are by non-academic actors. This is why one of the prospects for the future is to publish more content in the form of interview transcripts, which is undoubtedly more conducive to the circulation of « points de vue ». This approach is initiated in this issue with the publication of three interviews reflecting three different points of view on the history and characteristics of the DD&T journal.